Reversible Axonal Dystrophy by Calcium Modulation in Frataxin-Deficient Sensory Neurons of YG8R Mice - Mollá, Belén; Muñoz-Lasso, Diana C.; Riveiro, Fátima; Bolinches-Amorós, Arantxa; Pallardó, Federico V.; Fernandez-Vilata, Angel; de la Iglesia-Vaya, María; Palau, Francesc; Gonzalez-Cabo, Pilar (Frontiers in Molecular Neuroscience, 2017)
Friedreich’s ataxia (FRDA) is a peripheral neuropathy involving a loss of proprioceptive sensory neurons. Studies of biopsies from patients suggest that axonal dysfunction precedes the death of proprioceptive neurons in a dying-back process. We observed that the deficiency of frataxin in sensory neurons of dorsal root ganglia (DRG) of the YG8R mouse model causes the formation of axonal spheroids which retain dysfunctional mitochondria, shows alterations in the cytoskeleton and it produces impairment of axonal transport and autophagic flux. The homogenous distribution of axonal spheroids along the neurites supports the existence of continues focal damages. This lead us to propose for FRDA a model of distal axonopathy based on axonal focal damages. In addition, we observed the involvement of oxidative stress and dyshomeostasis of calcium in axonal spheroid formation generating axonal injury as a primary cause of pathophysiology. Axonal spheroids may be a consequence of calcium imbalance, thus we propose the quenching or removal extracellular Ca2+ to prevent spheroids formation. In our neuronal model, treatments with BAPTA and o-phenanthroline reverted the axonal dystrophy and the mitochondrial dysmorphic parameters. These results support the hypothesis that axonal pathology is reversible in FRDA by pharmacological manipulation of intracellular Ca2+ with Ca2+ chelators or metalloprotease inhibitors, preventing Ca2+-mediated axonal injury. Thus, the modulation of Ca2+ levels may be a relevant therapeutic target to develop early axonal protection and prevent dying-back neurodegeneration.